Semantic Repetition in Translating between Arabic and English - الشريف, Mohammed (مجلة العلوم الإنسانية والتطبيقية, 2016)
Languages are important medium for communication between nations. They are naturally distinctive. Arabic and English are among these languages which belong to two distant language families. Arabic is a Semitic language whereas, English is Anglo–Saxon. Accordingly, they are different. Several linguistic features pose variable problems when translating between these two languages. Semantic repetition in Arabic is among the problems which encounter professional as well as trainee translators when translating from Arabic into English. Despite the attempts by many translation researchers to deal with the problems encountered translators when translating, only a few investigated the problem of semantic repetition in Arabic This paper is an attempt to shed light on this translation problem using examples to illustrate it and explore the possible techniques suggested by translation scholars to tackle this and help to produce satisfactory translation to the target language reader of English. The discussions in this paper, could provide a point of reference for many translation researches throughout the Arab world.